Responsibility of the operator for the operation of the unmanned aerial vehicle - selected issues - Agnieszka Fortońska (Przegląd Komunikacyjny)
Abstract: The article presents the issue of responsibility for the use of unmanned aerial vehicles. As part of the study, selected domestic and foreign regulations will be analyzed. The author will present selected legal regulations of the European Union Member States: Poland and Croatia. Moreover, the laws of Canada and the United States will be discussed. Keywords: Drone; Civil liability; Criminal Liability